Pre-eruptive timescales from the historical Hapaimamo eruption at Mauna Loa, Hawai‘i - Couperthwaite, Fiona K.; Morgan, D. J.; Harvey, J.; Kahl, Maren (Journal of volcanology and geothermal research, 2022)
The 240 yr B.P. Hapaimamo eruption occurred on the southwest rift zone (SWRZ) of Mauna Loa. A large tephra deposit and an extensive lava flow field were produced that extend from 1880 m above sea level down to the southwest coast. Detailed petrological study of olivine crystals from both deposit types are used to determine the timescales of crystal disaggregation from a cumulate mush zone. Over 70% of studied olivines in both, lava flow and tephra samples, exhibit normal zoning. Tephra and flow olivine core compositions are between Fo89-84 and Fo89-81. Olivine rims in the tephra have compositions of Fo86-81, whereas rims in the flow samples extend to lower values within the range Fo83-71. The remaining tephra olivines are unzoned and fall within the same core compositional range. Using FeMg interdiffusion chronometry, we calculate tephra olivine diffusion timescales from 13 to 1600 days (days to years), with over 70% of timescales <100 days, and lava flow olivine diffusion timescales from 25 to 1110 days with 65% of timescales >100 days. Zoning widths were defined as narrow (type I) or broad (type II) and together with the diversity of timescales indicate an ongoing process of crystal mush disaggregation into the erupted host melt. Comparison of tephra and flow diffusion timescales show consistently longer timescales across the lava flow population, as expected due to continued diffusive re-equilibration. Our results suggest that where textural evidence allows, and tephra timescales can be compared, olivines from lava flows can be used to provide temporal information for magmatic processes within the subsurface and the lava flow. Comparison of published elemental diffusion timescales between Mauna Loa and neighbouring Kīlauea suggest that magma mobilisation and transfer processes occur over similar timescales within the plumbing systems of both Mauna Loa and Kīlauea.